Effectiveness of project-based learning in improving nahwu learning outcomes - Sri Indah Lestari; Yasmadi; Zuashfiyailina; Zaimatuz Zakiyyah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Based on the results of Nahwu's initial ability assessment of students, only 7.8% of students passed the minimum completion criteria (KKM). This data indicates that students do not understand Nahwu science well. For this reason, Project Based Learning (PjBL) is applied in learning to determine its effectiveness in improving student Nahwu learning outcomes. In this regard, researchers used a quasi-experiment method type one group pre-test post-test because the data came from students in the 3rd grade of Arabic Language Education (PBA) D for the 2023/2024 academic year, totaling 38 students. This data was collected through observation, interviews, tests and documentation techniques. Then, the data was analyzed using a paired sample t-test to determine students' Nahwu learning outcomes before and after using PjBL and N-Gain Score to determine their effectiveness in improving students' Nahwu learning outcomes. The research results show that PjBL is quite effective in improving student Nahwu learning outcomes.